A mixed methods study of clinician reported challenges in the assessment of ADHD and treatment decisions for children with ADHD in Brazil. (April 2021) - Honorio Neto, Fabiola; Camargo, Ana Paula; Polanczyk, Gilherme; Adamis, Dimitrios; McNicholas, Fiona
Objective: This ADHD national survey has obtained original data on the assessment and treatment of attention deficit hyperactivity disorder (ADHD) reported by Brazilian paediatricians and child psychiatrists; and has compared their practice.Method: The study questionnaire was delivered to 165 neuro/community paediatricians and 272 child and adolescent psychiatrists. Quantitative and qualitative data were collected and analysed.Results: Paediatricians assess children with a suspected ADHD, but do not feel confident to prescribe methylphenidate alone. Both paediatricians and child psychiatrists consider combined treatment of medication and psychotherapy more effective. Clinicians want to involve other professionals in the medical decisions but experience difficulties accessing specialist services, especially in public practice.Conclusion: This study showed the impact of the public–private mix in the delivery of and access to appropriate assessment and treatment services for children with ADHD in Brazil.